Identification of a Small Molecule Anti-biofilm Agent Against Salmonella enterica - Moshiri, Jasmine; Kaur, Darpan; Hambira, Chido M.; Sandala, Jenna L.; Koopman, Jacob A.; Fuchs, James R.; Gunn, John S. (Frontiers in Microbiology, 2018)
Biofilm formation is a common strategy utilized by bacterial pathogens to establish persistence in a host niche. Salmonella enterica serovar Typhi, the etiological agent of Typhoid fever, relies on biofilm formation in the gallbladder to chronically colonize asymptomatic carriers, allowing for transmission to uninfected individuals. S. enterica serovar Typhimurium utilizes biofilms to achieve persistence in human and animal hosts, an issue of both clinical and agricultural importance. Here, we identify a compound that selectively inhibits biofilm formation in both S. Typhi and S. Typhimurium serovars at early stages of biofilm development with an EC50 of 21.0 and 7.4 μM, respectively. We find that this compound, T315, also reduces biofilm formation in Acinetobacter baumannii, a nosocomial and opportunistic pathogen with rising antibiotic resistance. T315 treatment in conjunction with sub-MIC dosing of ciprofloxacin further reduces S. enterica biofilm formation, demonstrating the potential of such combination therapies for therapeutic development. Through synthesis of two biotin-labeled T315 probes and subsequent pull-down and proteomics analysis, we identified a T315 binding target: WrbA, a flavin mononucleotide-dependent NADH:quinone oxidoreductase. Using a S. Typhimurium strain lacking WrbA we demonstrate that this factor contributes to endogenous S. enterica biofilm formation processes and is required for full T315 anti-biofilm activity. We suggest WrbA as a promising target for further development of anti-biofilm agents in Salmonella, with potential for use against additional bacterial pathogens. The development of anti-biofilm therapeutics will be essential to combat chronic carriage of Typhoid fever and thus accomplish a meaningful reduction of global disease burden.